Experiences of Delinquent Children of Incarcerated Parents - Bael-Bisnar, Desseyme; Pioquinto, Paulino V. (Future Science / FSH-PH Publications, 2025)
This study investigated the experiences of delinquent children of incarcerated parents. The findings of this study served as supplementary guidelines for appropriate interventions and programs to minimize the delinquency of children of incarcerated parents. This study employed a qualitative research approach, specifically the phenomenological method. This inquiry utilized ten (10) informants from Lapu-Lapu City, Cebu, Philippines. Using a validated interview guide with open-ended questions prepared by the researcher, the informants were all interviewed individually. Colaizzi’s thematic analysis was used to analyze the data collected. Three themes summarized the positive experiences of the informants. These were: Overcoming Adversities Through Support System, Perseverance in the Midst of Despair, and Optimism Towards Survival. As to the negative experiences, the themes revealed were: Victim of Misfortune, Susceptible to Destruction, and Demotivated by the Daunting Challenges. The theme of Scarcity of Resources and Lack of Guidance highlighted the push factors of the informant’s delinquency. The study suggests that government organizations and the community work together to improve support systems and programs for children of incarcerated parents. This will help their well-being, prevent delinquency, and uphold their rights.